2013
DOI: 10.1521/jscp.2013.32.4.424
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Stress Generation: Examination of Interpersonal Predictors

Abstract: Researchers have consistently found that women are twice as likely to be depressed as men (as reviewed in Nolen-hoeksema & hilt, 2009). one possible mechanism for this relationship is that women experience more interpersonal stressful life events for which they played a part in their occurrence, a process called stress generation (hammen, 2003). The present study investigated two interpersonal predictors of depression-neediness and co-rumination-as mediators of the relationship between gender and stress genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 55 publications
5
27
0
1
Order By: Relevance
“…The findings are consistent with a number of previous studies [2, 8, 15, 16, 28, 35-37, 42, 47, 52] which also showed that women had greater reactivity compared to Victimization and employment/finance problems were not included in the adjusted analyses due to the absence of statistically significant associations between these outcomes and gender in men across a number of life event domains of: interpersonal relationships [8,16,28,35,47]; family/home stressors [2,15,35,42,45,52] and health problems [29,35]. No statistically significant gender difference was found for victimization which is inconsistent with the literature [29,37].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings are consistent with a number of previous studies [2, 8, 15, 16, 28, 35-37, 42, 47, 52] which also showed that women had greater reactivity compared to Victimization and employment/finance problems were not included in the adjusted analyses due to the absence of statistically significant associations between these outcomes and gender in men across a number of life event domains of: interpersonal relationships [8,16,28,35,47]; family/home stressors [2,15,35,42,45,52] and health problems [29,35]. No statistically significant gender difference was found for victimization which is inconsistent with the literature [29,37].…”
Section: Discussionsupporting
confidence: 90%
“…First, this study employed a wide range of life event domains to examine gender differences in associations between life events and distress. In contrast, other studies have generally limited examination to specific life event domains such as: interpersonal relationship difficulties [8,16,28,47]; family and home stressors [2,42,52]; and serious health problems [45]. Comparison across domains within the same data set allows a more comprehensive examination of possible gender differences, with individuals serving as their own controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did so because there is evidence that women's increased rates of depression may be accounted for, in part, by increased sensitivity to stress, particularly interpersonal stress (Bouchard & Shih, 2013;Oldehinkel & Bouma, 2011;Rose & Rudolph, 2006;Rudolph & Conley, 2005;Stroud, Salovey, & Epel, 2002). Thus, because the depression-interpersonal reactivity link is different (and stronger) for women than men, we focused exclusively on women in order to obtain a sample size sufficiently powered to test hypotheses.…”
mentioning
confidence: 99%